Six new polyphenolic metabolites isolated from the Suillus granulatus and their cytotoxicity against HepG2 cells - Zhao, Hanyu; Xiong, Miaomiao; Yang, Xiaomin; Yao, Lan; Wang, Zeyan; Wang, Li-an; Li, Zhuang; Zhang, Jinxiu; Lv, Jianhua (Frontiers in Nutrition, 2024)
Six new polyphenolic metabolites suillusol A-D (1-4), suillusinoic acid (5), ethyl suillusinoate (6), were isolated from the Suillus granulatus. The structures of new compounds were elucidated using high-resolution electrospray ionization mass spectroscopy, nuclear magnetic resonance data, and single-crystal X-ray diffraction analysis. As far as we know, compound 1 represents an unprecedented type of natural product and compound 3 represents a new type of polyphenol fungal pigment, which may be biosynthetically related to thelephoric acid. The cytotoxicity against HepG2 cells of the new compounds were also evaluated. Compound 2 demonstrate significant inhibitory activity against HepG2 cells with IC50 values of 10.85 μM, surpassing that of positive control cisplatin. Moreover, compound 1 and 3 also exhibited moderate cytotoxic activity with their IC50 values measured at 35.60 and 32.62 μM, respectively.